Implementasi Model Pembelajaran Doscovery Learning pada Pembelajaran Keterampilan Berbicara di SD Inpres Kompleks BTN IKIP - Rosdiah Salam; St. Nursiah B; Muh. Faisal (Seminar Nasional LP2M UNM, 2019)
Indonesian language skills are four interrelated skills namely listening skills, speaking skills, reading skills, and writing skills. Of the four skills, one of the most important language skills in daily life is speaking skills which are an effective oral communication medium. As Tarigan, (2008: 3) says "speaking is language" Speaking skills in elementary school are the core of the language learning process in schools, because with learning to speak students can communicate inside and outside the classroom in accordance with their development. This fact becomes the foundation in the effort to implement the Discovery Learning learning model to see the extent of its effect on speaking skills. The goal to be achieved is to find a picture of the application of the Discovery Learning learning model in Indonesian Language learning. To find out the picture of the results of students' speaking skills at SD Inpres BTIP IKIP Complex, Rappocini District, Makassar City. To determine the effect of the application of the Discovery Learning learning model to students' speaking skills at SD Inpres BTN IKIP Complex, Rappocini District, Makassar City. The results showed that the application of the Discovery Learning learning model affected the speaking skills of students at SD Inpres BTIP IKIP Complex, Rappocini District, Makassar City. This is proven by statistical analysis using the Paired Sample t-Test showing that the value of Sig. (2-tailed) is smaller than 0.05, which means that Ho is refused Ha accepted. It is recommended to use innovative learning models in learning.